Challenging Pan Activity in UK and Central Europe - Unknown (Guardian)
Terrence "Terry" Noel, founder and leader of the BT Melodians has been busily involved in a project funded by the Performing Rights Society of the UK. Noel's BT Melodians Steel Orchestra was selected to participate in the scheme called Adopt a Composer, which will see the ensemble interpreting the music of a selected composer. Additionally, Noel was in Belgium tutoring 40 young music students from Ossett Academy from West Yorkshire in the rudiments of pan skills.
Keywords: Steel bands (Music) -- Trinidad and Tobago; Musicians -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Music -- Instruction and study